The development of government support for compliance managers training in Russian Federation - Kazakov, Alexander Sergeevich; Prodanova, Natalia Aлексеевна; Sotnikova, Lyudmila Viktorovna; Plaskova, Nataliya Stepanovna; Prokofieva, Elena Vasilievna; Khamkhoeva, Fatima Yahievna (Linguistics and Culture Review, 2021)
The article reflects ?n the problems of government support for the training of compliance officers in the Russian Federation. This problem became more acute in connection with the consolidation in clause 3 of the Order of the Government of the Russian Federation No. 1697-r of August 16, 2018, the requirement to create internal systems under state and municipal authorities, ensuring that their activities comply with the requirements of antimonopoly legislation. The lack of theoretical and practical knowledge of civil servants in this area (the area of compliance) determines the relevance of the problem under consideration. This mostly concerned t? yesterday's students who are unable to provide payment ?f additional education in this area due to lack of financial resources. This entails the lack of qualifications of civil servants in the area of compliance and the ineffectiveness of compliance programs they are running. In the course of the study, we concluded that it is necessary to adopt in Russia a Scandinavian approach of government support for the training of labor resources at the expense of the national budget and taking into account the real need for labor resources in regions and municipalities.